2019
DOI: 10.21577/0103-5053.20190171
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Energy Calibration: A Practical Method for Determination of Macro and Micro Nutrients in Meat by ICP OES

Abstract: The multi-energy calibration (MEC) was evaluated for the determination of Ca, Cu, Fe, K, Mg, Na, P, S, and Zn in meat samples by inductively coupled plasma optical spectrometry (ICP OES). This calibration method consists of using only two calibration standards and several atomic and ionic emission wavelengths with different sensitivities to determine the analyte concentration in the sample. Both calibration mixtures are prepared using the same amount of sample, which contributes to minimize matrix effects. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(30 reference statements)
2
4
0
Order By: Relevance
“…Fe in raw beef topside (37.52 ± 1.58 mg/kg) is higher than raw beef (16 ± 2 to 25 ± 8 mg/kg) obtained in Zurich [28], and close to the value obtained by other Brazilian studies for beef (48 ± 2 mg/kg) [27]. On the other hand, the Fe content in pork loin (5.18 ± 0.26 mg/kg), chicken breast (4.58 ± 0.76 mg/kg), and lamb shank (18.76 ± 0.19 mg/kg) is lower than the content obtained in pork loin (7 ± 6 mg/kg), chicken breast without skin (5 ± 2 mg/kg), and lamb chop (20 ± 7 mg/kg) quantified in Zurich [28].…”
Section: Iron (Fe)supporting
confidence: 79%
See 3 more Smart Citations
“…Fe in raw beef topside (37.52 ± 1.58 mg/kg) is higher than raw beef (16 ± 2 to 25 ± 8 mg/kg) obtained in Zurich [28], and close to the value obtained by other Brazilian studies for beef (48 ± 2 mg/kg) [27]. On the other hand, the Fe content in pork loin (5.18 ± 0.26 mg/kg), chicken breast (4.58 ± 0.76 mg/kg), and lamb shank (18.76 ± 0.19 mg/kg) is lower than the content obtained in pork loin (7 ± 6 mg/kg), chicken breast without skin (5 ± 2 mg/kg), and lamb chop (20 ± 7 mg/kg) quantified in Zurich [28].…”
Section: Iron (Fe)supporting
confidence: 79%
“…In Southern Italy, the mean values of Mg found in raw lamb meat samples ranged between 25.80 ± 5.67 and 37.24 ± 2.27 mg/kg [ 49 ]. When comparing Mg levels presented in Table 6 with those obtained in other studies [ 26 , 27 , 48 , 49 ], we found that metal concentrations in the meat cuts that we reported are far superior.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…The feasibility of MEC has been demonstrated in the analysis of complex-matrix samples such as animal food and mineral supplements with high silicon content, liquid crystal displays, permanent hard disk magnets and ferrous nickel ores using laser-induced breakdown spectroscopy (LIBS), 13–15 fertilizers and milk by high-resolution continuum source molecular absorption spectrometry (HR-CS MAAS), 16 permanent magnets by dispersive X-ray fluorescence spectrometry, 17 biodiesel by UV-vis molecular absorption spectrometry, 18 meat, urine, medicinal plants and biomass residues by ICP-OES. 19–21…”
Section: Introductionmentioning
confidence: 99%